3D TiO2/ZnO composite nanospheres as an excellent electron transport anode for efficient dye-sensitized solar cells. Issue 56 (25th May 2016) - Cheng, Pengfei; Wang, Yinglin; Xu, Luping; Sun, Peng; Su, Zisheng; Jin, Fangming; Liu, Fengmin; Sun, Yanfeng; Lu, Geyu
Abstract : The present study aimed to develop a high electron lifetime ( τ r ) and low transit time ( τ d ) photoanode material for dye sensitized solar cells (DSSCs). Abstract : The present study aimed to develop a high electron lifetime ( τ r ) and low transit time ( τ d ) photoanode material for dye sensitized solar cells (DSSCs). An innovative material structure, a TiO2 /ZnO composite oxide hierarchical nanosphere, was synthesized by a two-step facile hydrothermal method. This composite oxide comprised 3D urchin-like TiO2 nanospheres and 1D ZnO nanospindles (ULTZ). The ZnO nanospindles were assembled onto the surface of the 3D urchin-like TiO2 in the hydrothermal process second step. A series of ULTZs made with different growth times were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The DSSCs based on the ULTZs exhibited much higher photoelectric properties and the energy conversion efficiency was 8.78%, which indicated a 30% increase in the conversion efficiency compared to those of the P25 electrode (6.79%); the great improvements of photoelectric properties and energy conversion efficiency for ULTZs based DSSCs were mainly attributed to the superior electronic transmission characteristics.